DIVERSITAS DAN POPULASI BAKTERI PELARUT FOSFAT PADA BERBAGAI PENGGUNAAN LAHAN DI UB FOREST - Heydiana Bunga Hutamy; Yulia Nuraini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
UB Forest has been converted into various uses such as agriculture and settlement. Land use conversion has an impact on decreasing soil organic matter, water quality, chemical properties and diversity of soil biota. Phosphorus is an essential nutrient for plants. But, its availability is very low, it is only 0.01% of the total P, because it is bound by the soil colloids. The aim of this study was to explore the difference of land uses and effect of enviroment to the diversity and population of phosphate solubilizing bacteria in the UB Forest. This study was conducted at various land uses i.e., protected area (KL), pine and coffee (PK), pine and annual crop (PS), mahogany and coffee (MK), and mahogany and annual crop (MS). Differences in land use significantly affected the population of phosphate solubilizing bacteria. The highest population of phosphate solubilizing bacteria was found in the plot of protected area (KL) of 103 x 106 cfu mL-1 and the lowest (7 x 106 cfu mL-1) was in the plot of pine and annual crop (PS).There were 11 bacterial isolates capable of dissolving phosphate sources in Pikovskaya media that were characterized by holozone with a ratio of 2.00 and 1.78. The suitable environment and sufficient substract can increase population of phosphate solubilizing bacteria.